2017
DOI: 10.1186/s13058-017-0858-x
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-200c and microRNA- 141 are regulated by a FOXP3-KAT2B axis and associated with tumor metastasis in breast cancer

Abstract: BackgroundMembers of the microRNA (miR)-200 family, which are involved in tumor metastasis, have potential as cancer biomarkers, but their regulatory mechanisms remain elusive.MethodsWe investigated FOXP3-inducible breast cancer cells, Foxp3 heterozygous Scurfy mutant (Foxp3 sf/+) female mice, and patients with breast cancer for characterization of the formation and regulation of the miR-200 family in breast cancer cells and circulation. Participants (259), including patients with breast cancer or benign breas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
94
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(99 citation statements)
references
References 57 publications
5
94
0
Order By: Relevance
“…In a study, Zhang et al (2017) could be used as diagnostic biomarkers for detection patients with early stage of breast cancer metastasis (Zhang et al, 2017).…”
Section: Micrornas and Exosomes As Diagnostic Biomarkers For Breastmentioning
confidence: 99%
“…In a study, Zhang et al (2017) could be used as diagnostic biomarkers for detection patients with early stage of breast cancer metastasis (Zhang et al, 2017).…”
Section: Micrornas and Exosomes As Diagnostic Biomarkers For Breastmentioning
confidence: 99%
“…Several studies have suggested that miRNAs could be suitable biomarkers [12][13][14][15] for early diagnosis of cancer, notably for its remarkable stability in liquid biopsies. In this context, although in its early stages, the use of EV-derived miRNAs (EV-miRNAs) from serum and plasma as a biomarker for BC have shown promising results [7,14,[16][17][18][19]. Among the EV-miRNAs described to be overexpressed in BC compared to control are miR-21, miR-1246 [7], and the miR-106a-363 cluster [14].…”
Section: Introductionmentioning
confidence: 99%
“…They usually negatively regulate a large of genes expression by binding to the 3’-untranslated region (3’-UTR) of target mRNAs [15]. Several studies have shown that miRNAs act as a means of anticancer and play an important role in regulating the invasion and migration of cancer [16-18]. Notably, recent studies revealed that a variety of miRNAs, including miR-152 [19], miR-381 [20], miR-211 [21], miR-223 [22] and so on, could inhibit tumor proliferation, invasion and metastasis in breast cancer by targeting various genes.…”
Section: Introductionmentioning
confidence: 99%